Lipid-based nutrient supplements do not decrease breast milk intake of Malawian infants. Issue 3 (24th December 2013) - Kumwenda, Chiza; Dewey, Kathryn G; Hemsworth, Jaimie; Ashorn, Per; Maleta, Kenneth; Haskell, Marjorie J
ABSTRACT: Background: The potential for small-quantity lipid-based nutrient supplements (LNS) to promote growth and development after 6 mo of age is currently being investigated. Because infants self-regulate energy intake, consumption of LNS may reduce breast milk intake and potentially decrease the beneficial effects of breast milk. Objective: The objective was to test the hypothesis that the breast milk intake of 9- to 10-mo-old rural Malawian infants receiving LNS would not be lower than that of infants receiving no supplementation. Design: This was a substudy of the International Lipid-based Nutrient Supplements (iLiNS) DOSE trial, in which 6-mo-old infants were randomly assigned to receive 10, 20, or 40 g LNS/d containing 56, 117, or 241 kcal/d, respectively, or no LNS until 18 mo of age. A subset was randomly selected to estimate breast milk intake at 9–10 mo of age with the dose-to-mother deuterium oxide dilution method. The noninferiority margin was <10% of total energy requirements. Results: Baseline characteristics ( n = 376) were similar across groups. The mean (±SD) daily breast milk intake of unsupplemented infants was 730 ± 226 g. The differences (95% CIs) in mean intake of infants provided with 10, 20, or 40 g LNS/d, compared with controls, were +62 (−18, +143), +30 (−40, +99), and +2 (−68, +72) g/d, respectively. Non–breast milk oral water intake did not differ by group ( P = 0.39) and was inversely ( r = −0.22, P < 0.01) associated with breast milk intake. Conclusion: In this rural Malawian population, breast milk intake at 9–10 mo of age was not reduced by supplementation with complementary foods with 10–40 g LNS/d. This study was a substudy within the iLiNS DOSE trial, which was registered at clinicaltrials.gov as NCT00945698.